Risk factors for survival after lung transplantation in cystic fibrosis: impact of colonization with multidrug-resistant strains of Pseudomonas aeruginosa - Weingard, Bettina; Becker, Sören L.; Schneitler, Sophie; Trudzinski, Franziska; Bals, Robert; Wilkens, Heinrike; Langer, Frank (Infection, 2025)
Lung transplantation is the ultimate treatment option for patients with advanced cystic fibrosis. Chronic colonization of these recipients with multidrug-resistant (MDR) pathogens may constitute a risk factor for an adverse outcome. We sought to analyze whether colonization with MDR pathogens, as outlined in the German classification of multiresistant Gram-negative bacteria (MRGN), was associated with the success of lung transplantation.